Rational Design of a Gd(III)–Cu(II) Nanobooster for Chemodynamic Therapy Against Cancer Cells - Shi, Xin-Ya; Shen, Ting-Xiao; Zhang, Ao-Lin; Tan, Li-Tao; Shen, Wen-Chang; Zhong, Hai-Jiang; Zhang, Shun-Lin; Gu, Yu-Lan; Shen, Lei (Frontiers in Chemistry, 2022)
Copper(II) containing coordination complexes have attracted much attention for chemodynamic therapy (CDT) against cancer cells. In this paper, the bimetallic nano-booster [Gd2Cu(L)2(H2O)10]·6H2O was prepared by a solvothermal method based on tetrazole carboxylic acid ligand H4L (H4L = 3,3-di(1H-tetrazol-5-yl) pentanedioic acid). And it showed considerable cytotoxicity towards three kind of human cancer cells (HeLa, HepG2 and HT29). MTT assay showed that the IC50 (half-maximal inhibitory concentration) of the complex NPs on HeLa cells (4.9 μg/mL) is superior to HepG2 (11.1 μg/mL) and HT29 (5.5 μg/mL). This result showed that [Gd2Cu(L)2(H2O)10]·6H2O NPs can inhibit cell proliferation in vitro, and may be potential candidates for chemodynamic therapy. In addition, the cytotoxicity was also confirmed by the trypan blue staining experiment. The results promise the great potential of Gd(III)-Cu(II) for CDT against cancer cells.